INFLUENCE POLICY OFFICE EMPLOYEES TO WORK PERFORMANCE REGIONAL SECRETARIAT OFFICE NORTH DISTRICT HALMAHERA - Soukotta, Fanrico; Rumapea, Patar; Ogotan, Martha (Sam Ratulangi University, 2016)
AbstractThis study was conducted based on the results pra survei that civil servants in performing basic tasks andfunctions indicated yet to reach optimum performance. This is presumably related to the implementation ofpolicy leadership. Thus, the study aims to “Assessing the impact of policy leadership on work performance ofemployees at the District Secretariat or North Halmahera District’. ‘This research applies descriptive method with quantitative approach. Purposive sample of respondentsassigned as many as 80 employees, and data collection techniques distributed questionnaires to obtainprimary data, secondary data obtained using thedocumentation techniques. All data and information obtained through surveys and direct observationtechniques. After the data is collected. and then analysed using percentages applying analytical techniques(frequency table), followed by product moment correlation analysis and simple linear regressionThe results showed that: Policy-led governing the internal regulations of the Organization at the highcategory, while performance is still in the category of medium or medium. The leadership of the verysignificant effect and makes a great contribution to the achievement of the employment. When leaders adoptpolicies that encourage employee creativity and innovation, it will improve their work performance.Thus, it can that the hypothesis that